Un-Australian Fictions : Nation, Multiculture(alism) and Globalisation, 1988-2008. - Pavlides, Eleni (Cambridge Scholars Publishing, 2013)
Un-Australian Fictions sets out to analyse a subset of Australian literary fictions published between 1988 and 2008 - from the bicentenary of British settlement to the global financial crisis and into a new millennium. During a new transnational era, Australians faced sober and unsettling times. Already accorded the status of national obsession, issues of national identity were vigorously contested. Concepts such as the nation, multiculturalism and globalisation became topics for heated discu ...